Question
upstudy study bank question image url

\begin{tabular}{l} Factor each completely. \\ \begin{tabular}{ll}\( x^{3}+1 \) & 2) \( 125-8 x^{3} \) \\ 3) \( 8 x^{3}-27 \) & 4) \( u^{3}-64 \) \\ 5) \( u^{3}-1 \) & \\ \hline\end{tabular} \\ \hline\end{tabular}

Ask by Gibbs Ward. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

Here are the factored forms of the given expressions: 1. \( x^{3} + 1 = (x + 1)(x^{2} - x + 1) \) 2. \( 125 - 8x^{3} = (5 - 2x)(25 + 10x + 4x^{2}) \) 3. \( 8x^{3} - 27 = (2x - 3)(4x^{2} + 6x + 9) \) 4. \( u^{3} - 64 = (u - 4)(u^{2} + 4u + 16) \) 5. \( u^{3} - 1 = (u - 1)(u^{2} + u + 1) \)

Solution

Certainly! Let's factor each expression completely using the formulas for sum and difference of cubes. ### 1) \( x^{3} + 1 \) This is a **sum of cubes**, which can be factored using the formula: \[ a^{3} + b^{3} = (a + b)(a^{2} - ab + b^{2}) \] Here, \( a = x \) and \( b = 1 \). Applying the formula: \[ x^{3} + 1 = (x + 1)(x^{2} - x \cdot 1 + 1^{2}) = (x + 1)(x^{2} - x + 1) \] ### 2) \( 125 - 8x^{3} \) This is a **difference of cubes**, recognizable as \( 5^{3} - (2x)^{3} \). Using the formula: \[ a^{3} - b^{3} = (a - b)(a^{2} + ab + b^{2}) \] Let \( a = 5 \) and \( b = 2x \). Thus: \[ 125 - 8x^{3} = (5 - 2x)(5^{2} + 5 \cdot 2x + (2x)^{2}) = (5 - 2x)(25 + 10x + 4x^{2}) \] ### 3) \( 8x^{3} - 27 \) Another **difference of cubes**, where \( (2x)^{3} - 3^{3} \). Applying the difference of cubes formula: \[ 8x^{3} - 27 = (2x - 3)((2x)^{2} + 2x \cdot 3 + 3^{2}) = (2x - 3)(4x^{2} + 6x + 9) \] ### 4) \( u^{3} - 64 \) This is a **difference of cubes** since \( u^{3} - 4^{3} \). Using the formula: \[ u^{3} - 64 = (u - 4)(u^{2} + u \cdot 4 + 4^{2}) = (u - 4)(u^{2} + 4u + 16) \] ### 5) \( u^{3} - 1 \) This is a **difference of cubes** with \( u^{3} - 1^{3} \). Applying the formula: \[ u^{3} - 1 = (u - 1)(u^{2} + u \cdot 1 + 1^{2}) = (u - 1)(u^{2} + u + 1) \] ### Summary of Factored Forms: 1. \( x^{3} + 1 = (x + 1)(x^{2} - x + 1) \) 2. \( 125 - 8x^{3} = (5 - 2x)(25 + 10x + 4x^{2}) \) 3. \( 8x^{3} - 27 = (2x - 3)(4x^{2} + 6x + 9) \) 4. \( u^{3} - 64 = (u - 4)(u^{2} + 4u + 16) \) 5. \( u^{3} - 1 = (u - 1)(u^{2} + u + 1) \) These factorizations use the standard formulas for factoring sums and differences of cubes.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

The expression \( x^{3}+1 \) can be factored using the sum of cubes formula: \( a^3 + b^3 = (a+b)(a^2 - ab + b^2) \). Here, \( a = x \) and \( b = 1 \). Therefore, it factors to \( (x+1)(x^2 - x + 1) \). For \( 125-8x^{3} \), this can be factored as a difference of cubes: \( a^3 - b^3 = (a-b)(a^2 + ab + b^2) \). Setting \( a = 5 \) and \( b = 2x \), the factorization becomes \( (5 - 2x)(25 + 10x + 4x^2) \). Now, looking at \( 8x^{3}-27 \), this is another difference of cubes. With \( a = 2x \) and \( b = 3 \), it factors to \( (2x - 3)(4x^2 + 6x + 9) \). The expression \( u^{3}-64 \) uses the same difference of cubes method, where \( a = u \) and \( b = 4 \). Thus, it factors to \( (u - 4)(u^2 + 4u + 16) \). Lastly, for \( u^{3}-1 \), we apply the difference of cubes again with \( a = u \) and \( b = 1 \), leading to the factorization \( (u - 1)(u^2 + u + 1) \). Happy factoring!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy